Impact of leisure satisfaction on perceived risk of infectious disease during the COVID-19 pandemic: evidence from new worker classes - Kim, Young-Jae; Ban, Young-Min; Kang, Seung-Woo (Frontiers in Public Health, 2024)
Introduction: This study examined how job market changes have affected individuals' leisure choices and satisfaction, focusing on worker classes that have undergone daily life changes (e.g., economic and social activities) due to the coronavirus disease (COVID-19) pandemic.Methods: A population-based cross-sectional study design was employed. South Korean workers aged 20-59 years answered an online survey administered from September 14 to October 4, 2021.Ultimately, 764 responses were used in the analysis. The measures used in this study consisted of factors affecting infectious disease risk perception and leisure satisfaction among the six new worker classes that emerged during the pandemic, according to socio-demographic status.Results: Among male participants, social, emotional, physical, environmental, and educational factors in leisure satisfaction were more strongly affected, with higher social, physical, and interpersonal relationships being factors in the perception of infectious disease risk. Among female participants, the interpersonal relationship factor of perceived risk was significantly affected by the social, emotional, and educational factors of leisure satisfaction. Interpersonal relationships (a factor in infectious disease risk perception), affected leisure satisfaction among members of Classes 1, 2, and 3, who experienced no change in pay. However, for the member of Class6 who experienced a decrease in pay, the economic factor negatively affected leisure satisfaction and played a pivotal role in our findings.Conclusion: This study verified the risk factors that inhibit leisure satisfaction among new worker classes that have emerged during the COVID-19 pandemic. Furthermore, the psychological health of people suffering pandemic-related financial constraints was affected, as they experienced a lower quality of life owing to reduced leisure activities and satisfaction.